#TITLE_ALTERNATIVE# - PRATAMA (NIM 13202105), EKKY
ITU-T H.264 / MPEG-4 (Part 10) Advanced Video Coding is the newest international video coding standard. The standard is resulted by collective effort of experts in the Joint Video Team (JVT) of ITU-T Video Coding Experts Group (VCEG) and ISO/IEC Moving Picture Experts Group (MPEG). Some highlighted features include on H.264/AVC. There are three main goals of the features: to improve prediction method, new design of picture structure and robustness to bitstream error. This Final Project discusses the analysis of some error robustness parameters. The parameters are slice size, macroblock ordering, intra macroblock and resend picture parameter sets (PPS). The analyze are about performance of encoder and the effect of parameter error. From analyze, it is shown that the increase of bit rate on slice representation is caused by changes on prediction mode. The increase is about 304 kbps or 113.43 % (compared with 1 slice per picture), reached when slice size is 1 macroblock. Variation of macroblock ordering doesn't influence the performance of encoder. The advantage of macroblock ordering is spreading error so that isn't focus on a region. The presence of intra macroblock result high robustness, but caused increase of bit rate about 50 kbps for 10 intra macroblock. On resend PPS parameter, it's needed increase of bit rate about 1.85 kbps.